2006
DOI: 10.2337/db05-1296
|View full text |Cite
|
Sign up to set email alerts
|

Differential Transmission of Type 1 Diabetes from Diabetic Fathers and Mothers to Their Offspring

Abstract: We studied the incidence of type 1 diabetes in the offspring of patients with childhood-and adolescent-onset type 1 diabetes and several risk factors predicting the risk. We defined the diabetes status in the offspring of all probands who were included in the nationwide register of Finnish type 1 diabetic patients diagnosed at the age of <17 years from 1965 T he incidence of childhood type 1 diabetes has increased globally over the past decades (1,2). The risk of type 1 diabetes in the offspring of diabetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 37 publications
5
65
1
3
Order By: Relevance
“…Thus, observed associations could in some cases be secondary to other variables not available in this analysis. The relatively marked reduction in the risk of developing islet autoantibodies found in children of mothers with type 1 diabetes is consistent with the established reduced diabetes risk in these children compared with children of fathers with type 1 diabetes [5][6][7] and an earlier cross-sectional study of islet autoantibody prevalence in children of parents with type 1 diabetes [29]. The reduced autoantibody risk appears to be specific for islet autoimmunity, since we saw no effect of maternal type 1 diabetes on the risk of transglutaminase autoantibodies (8 year risk 3.8% in children of mothers with type 1 diabetes vs 2.8% in children of fathers with type 1 diabetes; data not shown).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Thus, observed associations could in some cases be secondary to other variables not available in this analysis. The relatively marked reduction in the risk of developing islet autoantibodies found in children of mothers with type 1 diabetes is consistent with the established reduced diabetes risk in these children compared with children of fathers with type 1 diabetes [5][6][7] and an earlier cross-sectional study of islet autoantibody prevalence in children of parents with type 1 diabetes [29]. The reduced autoantibody risk appears to be specific for islet autoimmunity, since we saw no effect of maternal type 1 diabetes on the risk of transglutaminase autoantibodies (8 year risk 3.8% in children of mothers with type 1 diabetes vs 2.8% in children of fathers with type 1 diabetes; data not shown).…”
Section: Discussionsupporting
confidence: 52%
“…A model that is potentially useful for investigating factors that affect islet autoimmunity and type 1 diabetes risk is presented in children of parents who have type 1 diabetes. Risk is up to twofold greater in children of fathers with type 1 diabetes than in children of mothers with type 1 diabetes [5][6][7]. This intriguing fact suggests that either differences in inheritability of paternal vs maternal susceptibility genes or maternal imprinting or maternal diabetes (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, these studies did not include type 1 diabetes. Our findings suggest that the role of FHD is equally strong for LADA as for type 2 diabetes but stronger than for type 1 diabetes, because only (18). Notably, no difference between maternal or paternal diabetes on the risk of type 1 diabetes was seen in the present study.…”
Section: Statistical Analysessupporting
confidence: 32%
“…Warrem et al and others over the years have observed that maternal type 1 diabetes is associated with a lower risk of type 1 diabetes in the offspring than paternal type 1 diabetes [19][20][21]. The risk is twofold greater in children of a father than a mother with type 1 diabetes [19,21,22].…”
Section: Discussionmentioning
confidence: 98%